Optimalisasi Social Media Marketing dalam Meningkatkan Brand Awareness Developer Properti di PT. Hazalem Citra Propertindo Palembang - Sandi Tumiwa; Chairunnisah Putri Ayu Ningsih (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
The development of digital technology has transformed the way marketing is communicated across various industrial sectors, including the real estate sector. Social media has become a strategic tool not only for product promotion but also for building a company's image and increasing brand awareness amidst increasingly fierce competition. This article aims to analyze how digital marketing strategies through social media can increase brand awareness for PT. Hazalem Citra Propertindo Palembang, based on reports from Student Professional Practice (PPM) activities. The method used is a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation during the internship period. The results indicate that the company has utilized various social media platforms such as Instagram, TikTok, Facebook, and WhatsApp Business as a means of property promotion. However, this utilization has been suboptimal due to limited human resources, a lack of consistency in content creation, limited funding for digital promotions, and a lack of regular social media performance evaluation. Therefore, a more planned, consistent, and data-driven digital marketing strategy is needed to maximize social media's potential to sustainably increase brand awareness.